ANALYSIS OF THE EFFECT OF EDUCATION LEVEL, WAGES, AND HOTEL OCCUPANCY RATES ON EMPLOYMENT IN THE HOTEL SUB-SECTOR IN KUTA VILLAGE - Ramadani, Anggun Putri; Wahidin, Wahidin; Handayani, Tuti (Journal of Finance, Economics and Business, 2024)
Research with the title of the education level impact analysis, wages and hotel rate on the deployment of labor in the resort sub in kuta village in order to analyze how much such variables affected the deployment of the hotel's sub labor sector in kuta village. This research suggests that: Partial and simultaneous education rate variables have a positive and significant impact on the deployment of the labor force of the hotel's sub in kuta village, a partial and significant impact on the deployment of the hotel's sub infrastructure labor in kuta village, and a simultaneous positive and significant civil-sector residence variable in kuta village.